Sustainable Development Goals (SDGs): Less is More! - Soares, Sergei Suarez Dillon (2015)
"The Sustainable Development Goals (SDGs) can be seen as the latest incarnation of a movement that started with the launch of the first Human Development Report (HDR) in 1990. Long before the first HDR, many thinkers had already strongly argued that GDP size and growth should not be considered the sole yardstick of development. Nevertheless, there is no doubt that the HDR and its companion, the Human Development Index (HDI), played a great role in mainstreaming the notion that development should result in better lives for people, something which GDP sheds little light upon. Although we surely cannot establish how much, it is fair to consider that the Millennium Development Goals (MDGs) benefited from the consensus, quickly formed in the international community, over the “people-centric” notion of human development." (...)